Education about gender-based violence: opportunities and obstacles in the Ontario secondary school curriculum. Issue 2 (17th February 2022) - Vanner, Catherine
ABSTRACT: This article examines the Ontario secondary school curriculum's inclusion of opportunities to teach about gender-based violence, drawing on analysis of the Social Sciences and Humanities, Canadian and World Issues, and Health and Physical Education curricula and seven teacher interviews. Analysis applies Feminist Critical Discourse Analysis to show that opportunities for teachers to address gender-based violence issues exist, but the use of discourses that emphasize critical engagement with gender-based violence concepts are limited to upper level optional courses. Given their prevalence in Canada, gender-based violence issues should be positioned in the curriculum as essential knowledge, and taught with recognition of the gendered, racialized, and colonial influences that shape both risk and response to gender-based violence.